Counterinsurgency without insurgency: Medellin in the 1960s (2022)
article describes the appearance of insurgency and counterinsurgencyin Medellin during the decade of the sixties of the 20th century. In the study, the city is observed in the frameworkof its irregular demographic growth, a result of the arrival of people coming from the countryside due to its industrialization and the armed conflict that had existed since 1948. It also takes into account the context of the Cold War, in which the theory of modernization was developed, which contained social development and security measures with which it was sought to contain socialism. Documents were revised that gave an account of the Colombian context and the defense policies, the security measures implemented by local security forces and the appearance in the press of deeds related to the insurgency. It is concluded that although there was panic that was exacerbated by the governments due to the supposed presence of powerful insurgent groups, which «obliged them» to unleash harshsecurity measures, the operative power of these, analyzed in the light of the actions manifested in the period studied, was weak. This is why more than being a real threat to the establishment, it was a strategy to maintain social order.